Legal Protection for Consumers against Misleading Advertising According to the Perspective of the Laws in Force - Yuniar Rahmatiar (SEAN Institute, 2024)
Misleading advertising is an action that can harm consumers, both financially and psychologically, because the information conveyed is not in accordance with the facts or misleads public perception. Based on Law Number 8 of 1999 concerning Consumer Protection, consumers have the right to obtain correct, clear, and honest information regarding the conditions and guarantees of the goods and/or services purchased. This study aims to analyze legal protection for consumers who are victims of misleading advertising (misleading This study uses a normative legal method with a legal approach (advertising) according to the perspective of the applicable laws and regulations in Indonesia. The results of the study indicate that legal protection for consumers from misleading advertisements in Indonesia is regulated by various laws, such as Law No. 8 of 1999 concerning Consumer Protection, Law No. 32 of 2002 concerning Broadcasting, and Law No. 40 of 1999 concerning the Press. However, although there are regulations prohibiting the dissemination of misleading information, the main challenge in its implementation lies in the fragmentation of regulations spread across various laws that are often unsynchronized and less detailed in providing sanctions. This makes the application of the rules inconsistent, so that business actors can take advantage of legal loopholes to spread inaccurate advertisements. Weak law enforcement by related institutions such as the National Consumer Protection Agency and the Indonesian Broadcasting Commission, as well as the lack of coordination between institutions, worsen the situation. In addition, low consumer legal awareness makes them less aware of their rights, so that misleading advertising practices continue without much challenge. The development of digital technology also adds to the complexity of supervision because advertisements are now distributed more widely and quickly through online platforms, which are not always easy to monitor by traditional regulators.